Analyzing American Democracy : politics and political science - Bond, Jon R.; Smith, Kevin B., 1963-; Andrade, Lydia M. (Lydia Maria) (New York: Routledge, 2022)
"Following one of the most contentious presidential administrations and elections in US history, there has never been a greater need for an American government text like this--evidence-based, critically thoughtful, and contemporary in tone and touch. This text teaches students to think analytically by presenting current political science theories and research in answering the engaging, big questions facing American politics today. It serves as an introduction to the discipline-covering the Constitution, political behavior, formal and informal institutions, and public policy--by reflecting the theoretical developments and types of empirical inquiry conducted by researchers. New to the Fourth Edition 2020 election data updates throughout. Strategic updates on the Covid-19 pandemic, the resulting economic crisis, and the reckoning with racial injustice. Covid-19 is considered both in terms of questions of federalism as well as public policy. Questions of social justice are examined in light of civil rights/liberties as well as in terms of policy. Coverage of the death of Supreme Court Justice Ruth Bader Ginsberg and the ensuing battle to confirm her replacement and alter the ideological balance of the Court. A new co-author coming to the book with award-winning experience in diversity and teacher education as well as research interests in the presidency, women and politics, and foreign policy"--
Includes bibliographical references and index.
Keywords: Democracy -- United States; United States -- Politics and government